KEDUDUKAN ANAK LAKI-LAKI YANG LAHIR DARI DUDA BERSTATUS PREDANA DI DESA ADAT CEPAKA, TABANAN - I Wayan Ari Nugraha Bendesa; I Ketut Sukadana; Ni Made Puspasutari Ujianti (CV. Lafadz Jaya, 2026)
The trace purposing for examine direction from second marriage involving widower with predana status in Cepaka Traditional Village and examine legal status of male child born from such marriage under Balinese customary law. This problem examined from this riset is how second marriage of widower with predana status conducted in Cepaka Traditional Village and what legal status of male child born from such second marriage under Balinese customary law. The study commited comfirmable legal study using sociological, statutory, conceptual, customary. The data obtained interviews with Bandesa Adat, family, from library riset, were direct use descriptive qualitative riset. For second marriage of widower predana status conducted without fulfilling obligation to report marriage to prajuru adat as required by Awig-Awig of Cepaka Traditional Village. Consequently, marriage is not accepted from customary law and classified as babaung/ambal-ambalan marriage. Male child born from such marriage legally categorized as astra or kewalon, thereby not acquiring status pratisentana and having no inheritance rights over customary ancestral property.